Pengembangan Buku Panduan Praktik Berbasis PJBL Sebagai Media Inovasi pada Mata Kuliah Pengantar Teknologi Matematika - yudho, Aang (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
Learning in the introductory mathematics technology course faces various challenges, especially in connecting theory with practical applications due to the difficulty of understanding abstract mathematical concepts. This shows the need for a more applicable and innovative learning guide. This study aims to develop a PjBL-based guidebook to the needs of the introductory mathematics technology course. The method applied is Research and Development (R&D). The development model used is the ADDIE model. In this study, the data collected was divided into two types, namely qualitative and quantitative data. Qualitative data was obtained from the stages of criticism, suggestions, and responses given by the material validator and media validator. Quantitative data was obtained through a filled-in response questionnaire. Data collection was carried out using a questionnaire using a Likert scale. The validation results showed that an average of 86.9% of this product was feasible. This practical guidebook is very flexible to use by various student characteristics and has an easy-to-understand interface or presentation structure. The trial results showed that overall 80% of this practical guidebook was classified as very good in supporting the student learning process, especially in terms of project activities and discussions. This book is ready to use in practicums and provides a strong foundation for students to develop their skills in real projects. Keywords: Development, Guidebook, PjBL, Mathematics Technology